CRITICAL PERFORMAMCE ANALYSIS OF A STAR COOKING UTENSIL EQUIPED WITH COLLECTOR AND TRACKER - JOLLY UPADHYAYA, KAPIL DEV SHARMA (International Journal of Advanced Science and Technology, 2019)
A star cooking utensil with parabolic reflector and pursuit device has been designed and made-up with the assistance of obtainable materials. The huntsman used is of electronic kind to form it a lot of economical. Experiments are performed to research preparation power, standardized preparation power, and temperature distinction. Plots of temperature distinction and preparation power and temperature distinction and standardized preparation power are created.